Pharmacognostic and Phytochemical Investigation On Root of Cadaba Farinosa Forsk - UMESH B. TELRANDHE,; S. HEMALATHA,; ANUJ MODI, (International Journal of Pharma and Bio Sciences, 2010)
According to ethanomedical information plant Cadaba farinosa, Forsk is commonly known as Indian Cadaba, has been widely treating various ailments such as in diabetes, anthelmintic, purgative and anti-inflammatory. Present work is related to pharmacognostic investigation of fresh, powdered and anatomical sections of root of Cadaba farinosa, Forsk were carried out to determine its macromorphological, micromorphological and chemomicromorphological profiles. These findings will be useful towards establishing pharmacognostic standards on identification, purity and quality.